The impact of stigma on HIV testing decisions for gay, bisexual, queer and other men who have sex with men: a qualitative study - Bradley E. Iott; Jimena Loveluck; Akilah Benton; Leon Golson; Erin Kahle; Jason Lam; José A. Bauermeister; Tiffany C. Veinot (BMC, 2022)
Abstract Background Stigmatization may prompt gay, bisexual, queer and other men who have sex with men (GBQMSM) to avoid or delay HIV testing. There has been little attention to GBQMSMs' perspectives about how stigma may influence their decisions about whether, where, and how often to get tested for HIV. Methods We conducted nine focus groups with 64 adult GBQMSM in Metropolitan Detroit, including HIV-negative men and people living with HIV (PLWH). Data were thematically analyzed deductively and inductively in three rounds. Results Three themes emerged regarding whether to get tested: (1) Perceived promiscuity, risk perceptions and HIV testing; (2) Fearing sexual rejection; and (3) Fearing friend and family member distancing and rejection. Themes concerning where to get tested included: (4) Conflating HIV testing and diagnosis; and (5) Seeking privacy and safety at specialized services. As for how often to get tested, themes included: (6) Reducing contact with healthcare providers due to intersectional stigma; (7) Responsibility and regular testing; and (8) HIV stigma and testing as routine care. Black participants articulated themes (3), (4), and (6) with greater frequency than other participants. Framing HIV testing as a personal responsibility may have created a "new stigma," with unintended consequences not observed with "routine healthcare" messaging. Conclusions GBQMSMs' perspectives indicate the potential for new foci for HIV testing promotion interventions based on stigma-related issues that they deem important. There is a need for interventions to challenge the "promiscuity" stereotype, and to reduce the sexual stigmatization of GBQMSM living with HIV/AIDS-especially online. Provider stigma requires both intervention and continued availability of specialized services. Future stigma-reduction interventions for Black GBQMSM could focus on building family support/acceptance, awareness of multiple testing options, and integrating LGBTQ-related issues into initiatives for racial justice in health care.